Anthocyanin accumulation in fruit crops: a multi-layered regulatory network integrating molecular, epigenetic, hormonal and environmental regulation - K. Anchana; S. Saraswathy; C. Rajamanickam; K. Venkatesan; M. Elayarajan; T. Anitha (Molecular Biology Reports, 2026)

Chemometric and computational structure–activity relationship analysis of Ziziphus jujuba and Nephrolepis cordifolia phenolics for antioxidant and antidiabetic potential - Anitha A․; Ponmurugan P․; Arunkumar D․; Vasantha Sakthi S․; Yamuna A․; Jeyapreethi S․ (South African Journal of Botany, 2026)

Differential expression of neurogenesis-relevant genes in the peripheral blood lymphocytes of children with polymicrogyria - Mary Iype; Mithran Omana Surendran; Jesmy James; Aadhira Raghu; Smriti Menon; Arya K. S; Gokul Babu; Rahul Kumminimana; Ayyappan Anitha (Next Research, 2026)

Pollen micromorphology and functional traits as indicators of genetic diversity in Elaeis spp. - M. Neema; S. Suresh; G. Somasundaram; S. G. Silpa; R. P. Premalatha; P. Anitha; G. M. Aswathy (Genetic Resources and Crop Evolution, 2026)

Meta-topolin Stimulates In Vitro Plantlet Generation from Embryonic Shoot Meristem Explants in Coconut (Cocos nucifera) - M. S. Namitha; M. Neema; M. K. Rajesh; M. P. Fathimath Zaeema; Krishna Prakash; K. S. Muralikrishna; Anitha Karun (Agricultural Research, 2026)

Assessment of the Diurnal Cycle of Sea Surface Temperature from Model Analysis Against Ship-Based Ocean Observations - Imranali M. Momin; S. K. Sahoo; Radharani Sen; Anitha Gera (Journal of the Indian Society of Remote Sensing, 2026)

Polyphenol-based therapeutics for glioblastoma: validation from In-vitro cell viability assay and integrated onco-omics computational analysis - Yogesh H S; Sadik Shaik; Sibghatullah Muhammad Ali Sangi; Krishna Swaroop; Sreeharsha Nagaraja; Anitha K N; Vipin Kumar Mishra; Santosh Prasad Chaudhary Kurmi; Subrata Nath; Shankar Thapa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

Ingenious design and application of ZnAl-LDH/BiOBr Z-scheme heterojunction for effective photocatalytic degradation of tetracycline in aqueous environment: Insight into mechanism and toxicity estimation - R. Janani; M. Kanagalakshmi; S. Gopika Devi; Anitha Pius (Process Safety and Environmental Protection, 2026)

Smoke-derived microplastics of polypropylene In Vitro proliferative impact on human lung adenocarcinoma cells: Physicochemical analysis and biological evaluation - Nivedita Jha; Angshita Das; Megha Prasanth; S. Daisy Precilla; R. Sivachandran; Rajaneesh Anupam; T.S. Anitha (Environmental Toxicology and Pharmacology, 2026)

Toxicity and antiproliferative activity assessment of a novel compound Zr I isolated from Zingiber roseum Rosc - Swarnalatha P.; Deepika Divya K.; Anjali Jha; Anitha M.; S. P. D. Ponamgi; Seema Kumari; Sujatha Peela (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Interplay of flux-controlled memristive synapse and Josephson junction properties in modified Morris–Lecar neuron dynamics - Mohanasubha Ramasamy; S. Senthamizh Selvi; Anitha Karthikeyan; S. Dinesh Vijay; Karthikeyan Rajagopal (Cognitive Neurodynamics, 2025)

Visible-light driven photocatalytic degradation of triphenylmethane and azo dyes using a graphene oxide reinforced pectin hydrogel - M. Kanagalakshmi; S. Subasini; Anitha Pius (Carbohydrate Polymers, 2025)

Nutritional profile of probiotic-enriched potato yogurt as a plant-based alternative to dairy yogurt - S. Anitha; A. Manivannan (Next Research, 2025)

Optimization of potato yogurt using response surface methodology: Exploring a non-dairy substitute - S Anitha; A Manivannan (Next Research, 2025)

Neuroprotective Potential of Chromium-D-Phenylalanine: Insights from Molecular Docking, Dynamics and Rotenone-Induced Parkinsonism in Rats - K. N. Anitha; Mohammed Mutahir; Shivsharan B. Dhadde; B. S. Gowrishankar; Vivek Chandramohan (Biological Trace Element Research, 2025)

Novel biosynthesized zinc selenite photocatalysts for enhanced degradation of oxytetracycline and Rhodamine B dye with antibacterial activity - A. Anitha; P. Ponmurugan; D. Arunkumar; C. S. Sumathi; M. Sathishkumar; T. Purushothaman (BioMetals, 2025)

Development of reverse transcription recombinase polymerase amplification assay for rapid diagnostics of Peanut mottle virus - B. Parameswari; P. Anbazhagan; A. Rajashree; G. V. Chaitra; Kavi Sidharthan; S. K. Mangrauthia; Faisal Yousuf; K. Anitha; Y. Prasanthi; B. Bhaskar; V. Celia Chalam; G. P. Singh (Physiology and Molecular Biology of Plants, 2025)

The synergistic anti-Warburg efficacy of temozolomide, metformin and epigallocatechin gallate in glioblastoma - Shreyas S. Kuduvalli; Daisy Precilla Senthilathiban; Indrani Biswas; Justin S. Antony; Madhu Subramani; T.S. Anitha (Toxicology and Applied Pharmacology, 2024)

Correction to: Repurposing of approved antivirals against dengue virus serotypes: an in silico and in vitro mechanistic study - S. H. Rashmi; K. Sai Disha; N. Sudheesh; Kavitha Karunakaran; Alex Joseph; Anitha Jagadesh; P. P. Mudgal (Molecular Diversity, 2024)

Repurposing of approved antivirals against dengue virus serotypes: an in silico and in vitro mechanistic study - S. H. Rashmi; K. Sai Disha; N. Sudheesh; Joseph Karunakaran; Alex Joseph; Anitha Jagadesh; P. P. Mudgal (Molecular Diversity, 2024)
Dengue is an emerging, mosquito-borne viral disease of international public health concern. Dengue is endemic in more than 100 countries across the world. However, there are no clinically approved antivirals for its cure. Drug repurposing proves to be an efficient alternative to conventional drug discovery approaches in this regard, as approved drugs with an established safety profile are tested for new indications, which circumvents several time-consuming experiments. In the present study, eight approved RNA-dependent RNA polymerase inhibitors of Hepatitis C virus were virtually screened against the Dengue virus polymerase protein, and their antiviral activity was assessed in vitro. Schrödinger software was used for in silico screening, where the compounds were passed through several hierarchical filters. Among the eight compounds, dasabuvir was finally selected for in vitro cytotoxicity and antiviral screening. Cytotoxicity profiling of dasabuvir in Vero cells revealed changes in cellular morphology, cell aggregation, and detachment at 50 μM. Based on these results, four noncytotoxic concentrations of dasabuvir (0.1, 0.25, 0.5, and 1 µM) were selected for antiviral screening against DENV-2 under three experimental conditions: pre-infection, co-infection, and post-infection treatment, by plaque reduction assay. Viral plaques were reduced significantly ( p < 0.05) in the co-infection and post-infection treatment regimens; however, no reduction was observed in the pretreatment group. This indicated a possible interference of dasabuvir with NS5 RdRp, as seen from in silico interaction studies, translating into a reduction in virus plaques. Such studies reiterate the usefulness of drug repurposing as a viable strategy in antiviral drug discovery. Graphical Abstract In this drug repurposing study, dasabuvir, a known anti-hepatitis C drug, was selected through virtual screening and assessed for its anti-dengue activity.

Microproteins unveiling new dimensions in cancer - S. Daisy Precilla; Indrani Biswas; T. S. Anitha; B. Agieshkumar (Functional & Integrative Genomics, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Cellulose acetate based-membrane supported by metal-organic frameworks for the removal of diclofenac and ciprofloxacin from polluted water - Ananthi P; Hemkumar K; Manikandan S; Anitha Pius (Groundwater for Sustainable Development, 2024)

Identification of sources of resistance and comparative metabolomic profiling of resistant and susceptible chilli germplasm to Meloidogyne incognita Race 1 - Prasanna Holajjer; T. P. Ahammed Shabeer; M. K. Mahatma; Z. Khan; S. R. Pandravada; N. Sivaraj; Anitha Kodaru; Anita Pardeshi (Australasian Plant Pathology, 2024)

Improved photocatalytic degradation of organic pollutants using green synthesized ZnO and Ni@ZnO NPs for environmental applications - N.S. Mohan; S. Bhuvaneswari; R. Anitha; V. Vijayalakshmi (Environmental Nanotechnology, Monitoring & Management, 2024)

Pixel Reduction of High-Resolution Image Using Principal Component Analysis - Ramachandran Radhakrishnan; Manimegalai Thirunavukkarasu; R. Thandaiah Prabu; G. Ramkumar; S. Saravanakumar; Anitha Gopalan; V. Rama Lahari; B. Anusha; Shaik Hasane Ahammad; Ahmed Nabih Zaki Rashed; Md. Amzad Hossain (Journal of the Indian Society of Remote Sensing, 2024)

The use of ultrasonication in producing potato-based milk, and to determine its proximate composition - Anitha. S; Manivannan. A (Food and Humanity, 2023)

Antioxidant activity, total phenolic content, and total flavonoid content of potato milk – A novel functional beverage developed as an alternative to cow milk - S. Anitha; A. Manivannan (Food and Humanity, 2023)

Processing of functional yogurt-like product from potato milk supplemented with probiotic bacteria and evaluation of its proximate composition - Anitha S; Manivannan A (Food and Humanity, 2023)

Ultrasound-assisted preparation of potato milk and optimizing the formulation via response surface methodology - Anitha S; Manivannan A (Food and Humanity, 2023)

Nutritional evaluation of potato milk produced by ultrasonication–A functional alternative for bovine milk - Anitha S; Manivannan A (Food and Humanity, 2023)

Drug Dissolution in Oral Drug Absorption: Workshop Report - Kimberly Raines; Payal Agarwal; Patrick Augustijns; Alaadin Alayoubi; Lucas Attia; Annette Bauer-Brandl; Martin Brandl; Parnali Chatterjee; Hansong Chen; Yuly Chiang Yu; Carrie Coutant; Ana Luisa Coutinho; et al. (The AAPS Journal, 2023)
The in-person workshop “Drug Dissolution in Oral Drug Absorption” was held on May 23–24, 2023, in Baltimore, MD, USA. The workshop was organized into lectures and breakout sessions. Three common topics that were re-visited by various lecturers were amorphous solid dispersions (ASDs), dissolution/permeation interplay, and in vitro methods to predict in vivo biopharmaceutics performance and risk. Topics that repeatedly surfaced across breakout sessions were the following: (1) meaning and assessment of “dissolved drug,” particularly of poorly water soluble drug in colloidal environments ( e.g. , fed conditions, ASDs); (2) potential limitations of a test that employs sink conditions for a poorly water soluble drug; (3) non-compendial methods ( e.g. , two-stage or multi-stage method, dissolution/permeation methods); (4) non-compendial conditions ( e.g. , apex vessels, non-sink conditions); and (5) potential benefit of having both a quality control method for batch release and a biopredictive/biorelevant method for biowaiver or bridging scenarios. An identified obstacle to non-compendial methods is the uncertainty of global regulatory acceptance of such methods.

A Simplified Isothermal Recombinase Polymerase Amplification Assay for Detection of Sugarcane bacilliform virus Infection - B. Parameswari; S. K. Sharma; L. Karthikaiselvi; Baby Wangkhem; K. Nithya; R. Viswanathan; G. P. Rao; V. Celia Chalam; K. Anitha (Sugar Tech, 2023)

Effect of coinfections on neurocognitive functioning among people with clade C HIV infection in Zambia - Lumbuka Kaunda; Mary S. Ngoma; J. Anitha Menon; Robert K. Heaton; Sara Gianella; Ajay R. Bharti; Scott Letendre; Michelli Faria de Oliveira; Knut A. Hestad (Journal of NeuroVirology, 2023)

Genetic mapping of drought tolerance traits phenotyped under varying drought stress environments in peanut (Arachis hypogaea L.) - Subhasini Ghosh; Supriya S. Mahadevaiah; S. Anjan Gowda; Sunil S. Gangurde; Mangesh P. Jadhav; Anil A. Hake; P. Latha; T. Anitha; V. P. Chimmad; Kiran K. Mirajkar; Vinay Sharma; Manish K. Pandey; et al. (Euphytica, 2022)

First record of Cactus virus X in Dragon Fruit (Hylocereus spp.) in India - B. Parameswari; Bhaskar Bajaru; N. Sivaraj; S. K. Mangrauthia; S. Nagalakshmi; V. K. Baranwal; Prasanna Holajjer; M. Srinivas; K. Anitha (Indian Phytopathology, 2022)

Influence of salinity on the meiofaunal distribution in a hypersaline lake along the southeast coast of India - Pandiya rajan R S; Anitha Gera; Ramu K; Ranga Rao V; Ramanamurthy MV (Environmental Monitoring and Assessment, 2022)

Fluorescein Based Fluorescence Sensors for the Selective Sensing of Various Analytes - Keerthana S; Bincy Sam; Louis George; Sudhakar Y. N; Anitha Varghese (Journal of Fluorescence, 2021)

First report on the association of ‘Candidatus Phytoplasma asteris’ with lethal wilt disease of coconut (Cocos nucifera L.) in India - Merin Babu; S. Thangeswari; A. Josephrajkumar; V. Krishnakumar; A. Karthikeyan; V. Selvamani; Mol Daliya; Vinayaka Hegde; H. P. Maheswarappa; Anitha Karun (Journal of General Plant Pathology, 2021)

Genetic and genomic resources, and breeding for accelerating improvement of small millets: current status and future interventions - M. Vetriventhan; Vania C. R. Azevedo; H. D. Upadhyaya; A. Nirmalakumari; Joanna Kane-Potaka; S. Anitha; S. Antony Ceasar; M. Muthamilarasan; B. Venkatesh Bhat; K. Hariprasanna; Amasiddha Bellundagi; Deepika Cheruku; et al. (The Nucleus, 2020)
Current agricultural and food systems encourage research and development on major crops, neglecting regionally important minor crops. Small millets include a group of small- seeded cereal crops of the grass family Poaceae . This includes finger millet, foxtail millet, proso millet, barnyard millet, kodo millet, little millet, teff, fonio, job’s tears, guinea millet, and browntop millet. Small millets are an excellent choice to supplement major staple foods for crop and dietary diversity because of their diverse adaptation on marginal lands, less water requirement, lesser susceptibility to stresses, and nutritional superiority compared to major cereal staples. Growing interest among consumers about healthy diets together with climate-resilient features of small millets underline the necessity of directing more research and development towards these crops. Except for finger millet and foxtail millet, and to some extent proso millet and teff, other small millets have received minimal research attention in terms of development of genetic and genomic resources and breeding for yield enhancement. Considerable breeding efforts were made in finger millet and foxtail millet in India and China, respectively, proso millet in the United States of America, and teff in Ethiopia. So far, five genomes, namely foxtail millet, finger millet, proso millet, teff, and Japanese barnyard millet, have been sequenced, and genome of foxtail millet is the smallest (423-510 Mb) while the largest one is finger millet (1.5 Gb). Recent advances in phenotyping and genomics technologies, together with available germplasm diversity, could be utilized in small millets improvement. This review provides a comprehensive insight into the importance of small millets, the global status of their germplasm, diversity, promising germplasm resources, and breeding approaches (conventional and genomic approaches) to accelerate climate-resilient and nutrient-dense small millets for sustainable agriculture, environment, and healthy food systems.

Multi-class diagnosis of Alzheimer’s disease using cascaded three dimensional-convolutional neural network - Manu Raju; Varun P. Gopi; V. S. Anitha; Khan A. Wahid (Physical and Engineering Sciences in Medicine, 2020)

Identification of Potential Carbonic Anhydrase Inhibitors for Glaucoma Treatment Through an In-Silico Approach - D. Anitha; M. Suganthi; S. Gnanendra; M. Govarthanan (International Journal of Peptide Research and Therapeutics, 2020)

Antidiabetic, lipid lowering and antioxidant potentiating effect of Canavalia species in high fat diet-streptozotocin induced model - K. Anitha; S. Mohana Lakshmi; S. V. Satyanarayana (Advances in Traditional Medicine, 2020)

Automated segmentation of optic disc using statistical region merging and morphological operations - K. S. Nija; C. P. Anupama; Varun P. Gopi; V. S. Anitha (Physical and Engineering Sciences in Medicine, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Role of Taurine Transporter in the Retinal Uptake of Vigabatrin - Anitha Police; Vijay Kumar Shankar; S. Narasimha Murthy (AAPS PharmSciTech, 2020)

Remediation of heavy metals and dyes from wastewater using cellulose-based adsorbents - Anitha George Varghese; Sherely Annie Paul; M. S. Latha (Environmental Chemistry Letters, 2019)

Correction to: Optimisation of a screening platform for determining IL-6 inflammatory signalling in the senescence-associated secretory phenotype (SASP) - Adam Rolt; Anitha Nair; Lynne S. Cox (Biogerontology, 2019)

Optimisation of a screening platform for determining IL-6 inflammatory signalling in the senescence-associated secretory phenotype (SASP) - Adam Rolt; Anitha Nair; Lynne S. Cox (Biogerontology, 2019)

Aflatoxin-lysine adducts in blood serum of the Malawian rural population and aflatoxin contamination in foods (groundnuts, maize) in the corresponding areas - Anitha Seetha; Emmanuel S. Monyo; Takuji W. Tsusaka; Harry W. Msere; Frank Madinda; Tiyamika Chilunjika; Ethel Sichone; Dickson Mbughi; Benson Chilima; Limbikani Matumba (Mycotoxin Research, 2018)

Increasing incidence of tomato big bud phytoplasma in Ranga Reddy District of Telangana State, India - Madhupriya; D. Anitha Kumari; D. S. Vennila; M. Narayana Bhat; G. P. Rao (Indian Phytopathology, 2018)

Biosurfactants produced by Bacillus subtilis A1 and Pseudomonas stutzeri NA3 reduce longevity and fecundity of Anopheles stephensi and show high toxicity against young instars - Punniyakotti Parthipan; Raja Kumaresan Sarankumar; Anitha Jaganathan; Pandian Amuthavalli; Ranganathan Babujanarthanam; Pattanathu K. S. M. Rahman; Kadarkarai Murugan; Akon Higuchi; Giovanni Benelli; Aruliah Rajasekar (Environmental Science and Pollution Research, 2018)

Microbial Stability of Pharmaceutical and Cosmetic Products - Huy Dao; Prit Lakhani; Anitha Police; Venkataraman Kallakunta; Sankar Srinivas Ajjarapu; Kai-Wei Wu; Pranav Ponkshe; Michael A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2018)

Depth of soil compaction predominantly affects rice yield reduction by reproductive-stage drought at varietal screening sites in Bangladesh, India, and Nepal - Suresh Prasad Singh; Abhinav Jain; M. S. Anantha; Santosh Tripathi; Subarna Sharma; Santosh Kumar; Archana Prasad; Bhawana Sharma; Biswajit Karmakar; Rudra Bhattarai; Sankar Prasad Das; Shravan K. Singh; et al. (Plant and Soil, 2017)

De novo assembly and characterization of global transcriptome of coconut palm (Cocos nucifera L.) embryogenic calli using Illumina paired-end sequencing - M. K. Rajesh; T. P. Fayas; S. Naganeeswaran; K. E. Rachana; U. Bhavyashree; K. K. Sajini; Anitha Karun (Protoplasma, 2016)

Co-composting solid biowastes with alkaline materials to enhance carbon stabilization and revegetation potential - Saikat Chowdhury; Nanthi S. Bolan; Balaji Seshadri; Anitha Kunhikrishnan; Hasintha Wijesekara; Yilu Xu; Jianjun Yang; Geon-Ha Kim; Donald Sparks; Cornelia Rumpel (Environmental Science and Pollution Research, 2016)

Remediation of arsenic-contaminated water using agricultural wastes as biosorbents - Muhammad Bilal Shakoor; Nabeel Khan Niazi; Irshad Bibi; Ghulam Murtaza; Anitha Kunhikrishnan; Balaji Seshadri; Muhammad Shahid; Shafaqat Ali; Nanthi S. Bolan; Yong Sik Ok; Muhammad Abid; Fawad Ali (Critical Reviews in Environmental Science and Technology, 2016)

Sulfur crosslinks from thermal degradation of chitosan dithiocarbamate derivatives and thermodynamic study for sorption of copper and cadmium from aqueous system - Soon Kong Yong; William M. Skinner; Nanthi S. Bolan; Enzo Lombi; Anitha Kunhikrishnan; Yong Sik Ok (Environmental Science and Pollution Research, 2016)

Evaluation of Serum Vitamin B12 Levels and Its Correlation with Anti-Thyroperoxidase Antibody in Patients with Autoimmune Thyroid Disorders - S. Jaya Kumari; Ganapathy Bantwal; Anitha Devanath; Vageesh Aiyyar; Madhuri Patil (Indian Journal of Clinical Biochemistry, 2015)

Sources, Distribution, Environmental Fate, and Ecological Effects of Nanomaterials in Wastewater Streams - Anitha Kunhikrishnan; Ho Kyong Shon; Nanthi S. Bolan; Ibrahim El Saliby; Saravanamuthu Vigneswaran (Critical Reviews in Environmental Science and Technology, 2015)

Standalone EST microsatellite mining and analysis tool (SEMAT): for automated EST-SSR analysis in plants - Naganeeswaran Sudalaimuthu Asari; Manimekalai Ramaswamy; Elain Apshara Subbian; Manju Kalathil Palliyarakkal; S. K. Malhotra; Anitha Karun (Tree Genetics & Genomes, 2014)

Simultaneous detection of groundnut rosette assistor virus (GRAV), groundnut rosette virus (GRV) and satellite RNA (satRNA) in groundnuts using multiplex RT-PCR - S. Anitha; E. S. Monyo; P. Okori (Archives of Virology, 2014)

Effect of Coal Combustion Products in Reducing Soluble Phosphorus in Soil II: Leaching Study - Balaji Seshadri; Nanthi S. Bolan; Anitha Kunhikrishnan; Girish Choppala; Ravi Naidu (Water, Air, & Soil Pollution, 2014)

Scope of novel and rare bulbiferous coconut palms (Cocos nucifera L.) - B. A. Jerard; M. K. Rajesh; S. A. Elain; K. K. Sajini; Shafeeq Rahman; T. P. Fayas; Anitha Karun (Genetic Resources and Crop Evolution, 2014)

A Study to Evaluate Lipid Profile in Treatment Naïve HIV Positive Patients - Anitha Devanath; Somdattaa Ray; Ravi Kumar; B. S. Prarthana (Indian Journal of Clinical Biochemistry, 2014)

Effect of Aspect Ratio on the Monotonic Shear Behaviour: Micromechanical Interpretations - S. D. Anitha Kumari; T. G. Sitharam (Geotechnical and Geological Engineering, 2013)

Antihypercholesterolemic and antioxidative effects of an extract of the oyster mushroom, Pleurotus ostreatus, and its major constituent, chrysin, in Triton WR-1339-induced hypercholesterolemic rats - Ramalingam Anandhi; Thangaraj Annadurai; Thirugnanasambandhar S. Anitha; Arumugam R. Muralidharan; Kalifulla Najmunnisha; Vasanthi Nachiappan; Philip A. Thomas; Pitchairaj Geraldine (Journal of Physiology and Biochemistry, 2013)

Effect of Clean Coal Combustion Products in Reducing Soluble Phosphorus in Soil I. Adsorption Study - Balaji Seshadri; Nanthi S. Bolan; Anitha Kunhikrishnan (Water, Air, & Soil Pollution, 2013)

Comparative Study on Precipitation Techniques for Protease Isolation and Purification from Labeo rohita Viscera - S. Geethanjali; Anitha Subash (Journal of Aquatic Food Product Technology, 2013)

Changes in structural attributes of plant communities along disturbance gradients in a dry deciduous forest of Western Ghats, India - K. Anitha; Shijo Joseph; E. V. Ramasamy; S. Narendra Prasad (Environmental Monitoring and Assessment, 2009)

Analysis of diversity and distribution of Jatropha curcas L. germplasm using Geographic Information System (DIVA-GIS) - N. Sunil; N. Sivaraj; K. Anitha; Babu Abraham; Vinod Kumar; E. Sudhir; M. Vanaja; K. S. Varaprasad (Genetic Resources and Crop Evolution, 2009)